Análise do conhecimento e das atividades educativas acerca da utilização dos assentos de segurança infantil na cidade de Cascavel, Paraná - Camboin, Franciele Foschiera (2010)
The use of child restraint systems in Brazil emerges as a challenge in prevention and health promotion of the population. The correct transportation of the child within the motor vehicle is an important measure to minimize damage in case of traffic accidents. The aim of this study was to evaluate the knowledge and orientation activities on the use of child safety seat by professional nurses, traffic officers, traffic agents and trainers of training centers of drivers. This study is exploratory descriptive. The subjects of this research were composed by 20 Instructors of Driving Training School, nurses of Primary Health Unit who performed child care, nursing Pediatric Unit and/or motherhood Unit, traffic police and traffic warden. The sample consisted of: 33 (47.14%) nurses, 16 (22.85%) instructors of the Instructors of Driving Training School, 11 (15.72%) traffic wardens and 10 (14.29%) police. A traffic study was approved by the Comitê de Ética em Pesquisa da Universidade Estadual de Maringá under the register 045093000-08. The results revealed that 29 (41.43%) people had post-graduate study, 21 (30%) middle school education, 18 (25.71%) higher education and 02 (2.86%) technical education. About subject, 38 (54.28%) were female and 32 (45.72%) were male. Almost half of the women (42.9%) knew of this study in part or denied knowledge information about the correct use of child safety seat, while 25.7% of men did not know (p = 0.042). Less than half of the subjects were able to point to the correct age for the use of child safety seat and more than 30 (45.7%) subjects could not answer how much weight was given to the proper use. Instructors, invest more time focusing on proper child restraint in cars, while the nurses are least likely to spend time guidelines, when compared to other professionals who said holding educational activities (p = 0.001 ). 30 (50%) professionals spend 15 minutes daily to focus on the use of child safety seat, these 20 (33.3%) were nurses. While 24 (40%) use 15 minutes to 2 hours and from these 12 (20%) were instructors. Only 6 (10%) said they used more than 2 hours with guidelines and 3 (5%) were traffic wardens (p = 0.000). Although the child safety seat make to the routine guidelines of most professionals, these professionals have incorrect or incomplete information about its use. Individual or group actions are activities in which education for car traffic must be present. We must rethink the way professionals are being informed and trained to conduct educational practices in the prevention of traffic accidents, and correct use of child safety seat, safe behavior in traffic, to prevent and promote state of health.